PENGARUH KUALITAS PELAYANAN, FASILITAS DAN HARGA TERHADAP KEPUASAN KONSUMEN HOMESTAY PONDOK MERAPI SELO - Latifah Izzati; Listyowati Puji Rahayu; Nuning Lisdiana (Universitas Boyolali, 2022)
This study aims to determine whether the quality of service, facilities and prices affect the satisfaction of homestay Pondok Merapi Selo customers. The population in this study were consumers who stayed at homestays in Pondok Merapi. Data collection technique through the distribution of questionnaires with a sample of 100 respondents. The research method is a quantitative method. Testing of data instruments is carried out with validity and reliability tests, for data analysis, normality tests, multicholinearity tests, heteroskedasticity tests, autocorrelation tests, and hypothesis tests are used to find out whether between variables have a significant relationship . The results showed that the service quality variable of calculated t value of 0.681 < t of table 1.984 and the sig value of 0.498 > of sig of 0.05 which means insignificant. While the facility variable partially t counts 2.879 > t table 1.984 and the sig value is 0.005 > 0.05 which means significant. And the price variable is partially calculated t value 2.879 > t table 1.984 and sig value 0.005 > sig 0.05 which means significant . The result of the F test calculated 36.634 > the value of the table F using the α ( alpha ) 0.05 or 5 % then Ho was successfully rejected and Ha was accepted. Ho's refusal is evidenced by the calculation results that the value of Sig ( 0.000 ) < of a ( alpha ) 0.05 so that it can be concluded that all independent variables simultaneously affect the independent variable, namely consumer satisfaction.